SUBTITLING STRATEGIES IN REAL STEEL MOVIE - Naomi Ventria Nauly Simanjuntak; Achmad Basari (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
The research is entitled Subtitling Strategies in Real Steel Movie. This study aims at finding out the strategies employed to translate the English subtitles into Indonesian subtitles, and identifying the strategy employed the most in the translated subtitles. The unit of analysis of this research is every utterance translated using the subtitling strategies in the Real Steel movie. The source language is English, and the target language is Indonesian as the data. This research used a descriptive qualitative method because the purpose of this study is to describe the phenomena of translation, especially the subtitling strategies employed in the Real Steel movie. The results of this research show that not all the subtitling strategies were employed. There are some subtitling strategies left unemployed, they were dislocation strategy, condensation strategy, decimation strategy, and resignation strategy. The other six strategies were employed by the translator in translating English subtitles in the Real Steel movie. The results show that there are 12 (19.35%) utterances of Expansion strategy, 11 (17.74%) utterances of Paraphrase strategy, 10 (16.12%) utterances of Transfer strategy, 10 (16.12%) utterances of Imitation strategy, 1 (1.61%) utterance of Transcription strategy, and 18 (29.03%) utterances of Deletion strategy. Deletion is the strategy which was employed the most by the translator in the movie. The deletion strategy was identified through the facts that there are words in the source language not maintained in the target language. There are also words in the source language not rendered in the target language. Meanwhile, Expansion is the strategy employed the most after the Deletion strategy. The Expansion strategy was employed because the strategy was naturally proven to help the target audience understand the subtitles more easily.Keywords: Translation, Subtitles, Subtitling Strategies